Implementation of Anti-Corruption Education Through Penetrasi Method (Penanaman 9 Nilai Karakter Anti Korupsi) for the Urban Village Community of Jabungan - Pritaningtias, Dina Wahyu; Barendriyas, Anindhita Sekaring; Sabela, Amira Rahma; Utari, Indah Sri (Indonesian Journal of Advocacy and Legal Services, 2019)
The importance of anti-corruption education for communities in the area of Jabunganan Village in particular among teenagers, because they were the agents of change for nation building Indonesia in order to form a generation that has integrity. Attempts are made to college student real work relating to the State University of Semarang 2019 in instilling the value of anti-corruption through the PENETRASI method (Penanaman Sembilan Nilai Karakter Anti Korupsi) by holding discussion, dissemination, training and games. In these efforts, contains multiple values, including the anti-corruption character: 1) Honest, 2) Fair, 3) Hard-work, 4) Caring, 5) Simple, 6) Daring, 7) Liability, 8) Independent, 9) Disciplines. These efforts include: Anti Corruption Week (Antik), Rumah Sampah (Ramah), Ruang Inspirasi (Rapi), dan Anti Suap (Asiap), Bank Sampah (Basah), Pelatihan Neraca Laba Rugi bagi UMKM, Lomba Pidato Tema Anti Korupsi (Ladang Tikus), Pelatihan Pembuatan Briket dari Sampah Organik, Psikodrama, Mitigasi Bencana, Infografis Anti Korupsi, Permainan Ular Tangga dan Festival Anak Sholeh.